2015
DOI: 10.4103/2249-4863.152258
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among persons with physical disability in udupi taluk: A cross sectional study

Abstract: Background:Disability is not just a health problem or attribute of individuals, but it reflects the problems individuals experience in their interaction with society and physical movements. Disabled persons remain neglected part of society and they also experience various barriers due to restriction of participation.Objectives:The aim was to assess the quality of life (QOL) of physically disabled persons, the impact of physical disability on activities of daily living (ADL) and to study the awareness about law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 4 publications
0
17
0
1
Order By: Relevance
“…Until now, QoL has been commonly used by many studies in different cultures to measure the relationships between QoL and specific health issues, such as obesity in children and adults [13], chronic illnesses, including hypertension, chronic obstructive pulmonary disease, and cardiovascular disease [9] [14] [15], elderly populations and postmenopausal women [16] [17], physical disability [18], and informal carers [19]. QoL has been found correlated with life satisfaction, sleep quality, and general health status [20].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, QoL has been commonly used by many studies in different cultures to measure the relationships between QoL and specific health issues, such as obesity in children and adults [13], chronic illnesses, including hypertension, chronic obstructive pulmonary disease, and cardiovascular disease [9] [14] [15], elderly populations and postmenopausal women [16] [17], physical disability [18], and informal carers [19]. QoL has been found correlated with life satisfaction, sleep quality, and general health status [20].…”
Section: Introductionmentioning
confidence: 99%
“…The Quality of Life indicator was used in seven studies. [ 42 43 44 45 46 47 48 ] All these referred to the term “quality of life” [ Table 5 ]. Only four studies defined it based on the WHO concept of quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies showed a decreased mean summary scores among women. [ 42 44 45 46 47 48 ] Two of the studies showed a significant association of quality of life with sex – women had lower mean scores than males. [ 42 46 ] All these studies showed that as age increased, the quality of life mean scores decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Houve uma fraca correlação entre a presença do cuidador no domicílio e melhores atividades de vida diária alcançadas entre as pessoas com deficiências. Estes achados se aproximam do estudo de Kuvalekar et al 18 , que reportaram 11,5% dos indivíduos com alguma incapacidade física que necessitavam de assistência, e mais distantes de Nigeria et al 19 , que reportaram 28,3% dos indivíduos que necessitavam de auxílio em pelo menos um domínio medido pelo índice de Barthel.…”
Section: íNdice De Barthelunclassified